Description and Contribution of Brain Magnetic Resonance Imaging in Nontraumatic Critically Ill Children. (December 2016) - Mortamet, Guillaume; Kossorotoff, Manoelle; Baptiste, Amandine; Boddaert, Nathalie; Castelle, Martin; Hubert, Philippe; Lesage, Fabrice; Renolleau, Sylvain; Oualha, Mehdi
Background: The authors aimed to collect all brain magnetic resonance imaging (MRI) performed in critically ill children in the authors' medical pediatric intensive care unit over a 2-year period (2012-2013) to (1) describe the findings and (2) assess its contribution on practical patient care. Methods: This is a single-center and retrospective study. All children without traumatic brain injury who underwent a brain MRI during pediatric intensive care unit stays were included. To assess the exam's contribution, the patient's medical condition at the time of the MRI exam was blindly and separately exposed to a pediatric neurologist and a pediatric intensivist. Results: During the study period, 87 patients (7.5%) underwent a brain MRI. Median age was 4 months and 13 children (14.9%) died in pediatric intensive care unit. The most common final diagnosis was postanoxic encephalopathy. Brain MRI was abnormal in 68 patients (78.2%). No serious adverse event occurred during the transport. The neurologist and the intensivist considered brain MRI as indicated during pediatric intensive care unit stay in 65 (74.7%) and 68 patients (78.2%). They deemed that brain MRI had a diagnostic contribution in 76 (87.4%) and 60 (69.0%) patients, respectively. A therapeutic change consecutive to MRI findings occurred in 19 patients (21.8%) and MRI results were associated with a decision to withdraw life-sustaining treatment in 21 patients (24.1%). Conclusion: Brain MRI is one component of neuromonitoring, and this study suggests a substantial diagnostic contribution, although its therapeutic impact appears limited to specific diagnoses.